Selection of modes and pressure regulation when pumping oil and oil products to save energy - V. V. Shalay; M. O. Myznikov; M. I. Gildebrandt; V. A. Grinevich (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article presents the results of a study related to the choice of modes and pressure regulation to save electricity. Calculations are carried out on the example of a technological section of a specific oil pipeline. The paper demonstrates an approach to assessing the economic efficiency of each of the flow control options to obtain the required performance. The above arguments and methods of selecting modes can be applied to any oil pipelines and product pipelines.